1994
DOI: 10.1007/bf00239885
|View full text |Cite
|
Sign up to set email alerts
|

Studies on plant regeneration from cotyledonary protoplasts in Brassica campestris

Abstract: Protoplasts isolated from both 7-day-old light-grown and 4-day-old dark/dim light-grown cotyledons of four Brassica campestris varieties (Arlo, Sonja, Bunyip and Wonk Bok) were cultured in three liquid media: modified K8P, modified MS and modified Pelletier's B to compare the capacities for cell division and plant regeneration. Following cell wall regeneration the cultured protoplasts from dark/dim light-grown cotyledons of four varieties showed rapid division and high frequency of cell division compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, plant regeneration has only been obtained in B. oleracea (Vatsya & Bhaskaran 1982;Lu et al 1982;Robertson et al 1983) and in B. carinata (Jaiswal et al 1990). Until the present study (Zhao et al 1994a), no plant regeneration has been reported from cotyledon protoplast culture in either Brassica napus or Brassica campestris though callus formation has been obtained in these two species (Lu et al 1982). From the present results, it can be concluded that the culture system used for plant regeneration from cotyledon protoplasts of B. napus, B. campestris and B. oleracea is simple, rapid and reproducible; a high regeneration capacity exists in B. campestris.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, plant regeneration has only been obtained in B. oleracea (Vatsya & Bhaskaran 1982;Lu et al 1982;Robertson et al 1983) and in B. carinata (Jaiswal et al 1990). Until the present study (Zhao et al 1994a), no plant regeneration has been reported from cotyledon protoplast culture in either Brassica napus or Brassica campestris though callus formation has been obtained in these two species (Lu et al 1982). From the present results, it can be concluded that the culture system used for plant regeneration from cotyledon protoplasts of B. napus, B. campestris and B. oleracea is simple, rapid and reproducible; a high regeneration capacity exists in B. campestris.…”
Section: Discussionmentioning
confidence: 69%
“…However, as reviewed in a previous paper (Zhao et al 1994a), although considerable progress in Brassica protoplast culture has been made since the late 1970's, plant regeneration from cotyledon protoplast culture remains a major problem for some Brassica species. Cotyledons play an important role in shoot regeneration and development from some tissues in vitro (Sharma et al 1991 .…”
Section: Introductionmentioning
confidence: 99%
“…At this time the embryos were transferred to solid BS medium containing 2% sucrose and 0.3% phytagel without growth regulators (Gamborg et al, 1968) and cultured at 25"C in a 8-10 h light period. It was observed that shoot and root induction was highly influenced not only by the culture conditions (media, light and temperature), but also by the genotype (Zhao et al, 1994). We found that plant growth regulators were not necessary in the culture medium.…”
Section: Plant Regenerationmentioning
confidence: 84%
“…Protoplasts isolated from the genus Brassica have been studied since the middle 1970's and considerable progress has been made in the development of culture techniques in this agricultural important genus. Until recently, no successful studies have reported the regeneration of plants from cotyledon protoplasts in both Brassica napus and B. campestris (Zhao et al 1994). Reports of plant regeneration from cotyledon protoplasts have been made for Brassica oleracea (Lu et al 1982;Vatsya & Bhaskaran 1982;Robertson et al 1988) and for B. carinata (Yang & Jia 1989).…”
Section: Introductionmentioning
confidence: 99%